Faktor - Faktor Risiko Yang Berhubungan Dengan Kejadian Ulkus Kaki Pada Penderita Diabetes Melitus: Literature Review - Hanifah Nur Jamilah, (2020)
Diabetic foot ulcer is a wound in the lower limb in people with diabetes mellitus. This study aims to determine the risk factors associated with the incidence of foot ulcers in people with diabetes mellitus and prevention of foot ulcers. This research uses the literature review research method and is conducted searching the literature using a database through PubMed, Science Direct, and Scopus. The results of 10 journals found 19 risk factors that were significantly related to the incidence of foot ulcers. Of the 19 risk factors, divided into three groups of risk factors associated with the incidence of foot ukus in people with diabetes mellitus. First, risk factors based on characteristics include age, gender, residence, economic status, Body Mass Index, waist circumference. Second, risk factors according to conditions and behavior related to diabetes mellitus include a history of diabetic foot ulcers and amputations, type of diabetes mellitus, diabetes mellitus therapy, duration of diabetes mellitus, glycemic control, and foot care. Third, risk factors according to concomitant diseases and changes in foot shape include peripheral neuropathy, nephropathy, retinopathy, peripheral arterial disease, dyslipidemia, foot deformity and callus formation in the legs. Conclusion: neuropathy and peripheral arterial disease are the most influential factors in the incidence of foot ulcers and their prevention by exercising glycemic control, nutritional diet, exercise, and foot care.